2022
DOI: 10.1037/fsh0000672
|View full text |Cite
|
Sign up to set email alerts
|

Promoting glycemic control in young children with type I diabetes: Results from a pilot intervention for parents.

Abstract: Objective: Nutrition and physical activity are key components of daily diabetes care in young children with type I diabetes (T1D). Normative developmental behavioral challenges related to nutrition and physical activity complicate management of T1D. The current pilot study evaluated the feasibility, acceptability, and indications of behavior change of an intervention aimed at improving nutrition and physical activity in young children with T1D. Method: Thirty-6 parents of young children (ages 2-5 years, M = 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…Participant recruitment was particularly challenging, with twelve patients approached for every one participant ultimately enrolled in the study. Response, recruitment, and retention rates were all lower than anticipated, considering that rates of trial participation among children with T1D seen at Children's National are typically higher than in the present study [30,31].…”
Section: Discussioncontrasting
confidence: 64%
“…Participant recruitment was particularly challenging, with twelve patients approached for every one participant ultimately enrolled in the study. Response, recruitment, and retention rates were all lower than anticipated, considering that rates of trial participation among children with T1D seen at Children's National are typically higher than in the present study [30,31].…”
Section: Discussioncontrasting
confidence: 64%
“…Lastly, a pilot RCT ( n = 36) tested the Type 1 Training (TOTs) program which aimed to improve nutrition and physical activity in 2–5 years olds with T1D [15 ▪ ]. TOTs consisted of 6 psychoeducation sessions (5 individual, 1 group) with a master's level clinical social worker, one session with a CDCES and the social worker, and parent peer coaching.…”
Section: Psychosocial and Behavioral Interventions For Children With ...mentioning
confidence: 99%
“…With respect to glycemia, nine studies reported favorable changes [12 ▪ ,13 ▪▪ ,14 ▪ ,15 ▪ ,22 ▪ ,23,26 ▪ ,28 ▪▪ ,30 ▪▪ ], seven found no change [9,10 ▪▪ ,16 ▪ ,18,19 ▪ ,21,31 ▪ ], and one reported an increase in HbA1c among intervention recipients [20 ▪ ]; five studies did not evaluate or report glucose metrics [8 ▪ ,24,25 ▪▪ ,27 ▪ ,29 ▪ ]. Psychosocial care is important independent of its relationship to glucose, and should be provided irrespective of the likelihood of improving glycemia.…”
Section: Overall Trends In Interventionsmentioning
confidence: 99%
See 1 more Smart Citation